"Investigación de mercado para la aceptación del aceite Sacha Inchi (Plukenetia volubilis L.) en la zona Quevedo". - Intriago Rodríguez, Irma Isabel (2013)
This investigation was conducted at Quevedo, located at province of Los Ríos in 2013. Its main objective was to implement a market research Sacha Inchi Oil, for product acceptance in the area. It was considered two specific objectives which are the current market diagnose Sacha Inchi Oil and determining consumer behavior. The hypothesis was that "The Sacha Inchi oil release will have a positive impact at the local market." Chapter two, the research supports the theoretical basis of several authors, starting with an overview of Sacha Inchi Oil, knowing what a market research and the processes to be followed, among these are the defining concepts as clear what is a market, analyzing the topic of demand and types of demand, supply and types of supply, price analysis, marketing analysis, distribution channels and product definition................................................